Molecular Mechanisms Underlying Sensory-Motor Circuit Dysfunction in SMA - Shorrock, Hannah K.; Gillingwater, Thomas H.; Groen, Ewout J. N. (Frontiers in Molecular Neuroscience, 2019)
Activation of skeletal muscle in response to acetylcholine release from the neuromuscular junction triggered by motor neuron firing forms the basis of all mammalian locomotion. Intricate feedback and control mechanisms, both from within the central nervous system and from sensory organs in the periphery, provide essential inputs that regulate and finetune motor neuron activity. Interestingly, in motor neuron diseases, such as spinal muscular atrophy (SMA), pathological studies in patients have identified alterations in multiple parts of the sensory-motor system. This has stimulated significant research efforts across a range of different animal models of SMA in order to understand these defects and their contribution to disease pathogenesis. Several recent studies have demonstrated that defects in sensory components of the sensory-motor system contribute to dysfunction of motor neurons early in the pathogenic process. In this review, we provide an overview of these findings, with a specific focus on studies that have provided mechanistic insights into the molecular processes that underlie dysfunction of the sensory-motor system in SMA. These findings highlight the role that cell types other than motor neurons play in SMA pathogenesis, and reinforce the need for therapeutic interventions that target and rescue the wide array of defects that occur in SMA.